Deteksi Dini Peningkatan Glukosa Dalam Darah di RW 07 Kelurahan Pekayon, Pasar Rebo - Dwi Agustina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Diabetes Mellitus is one of the chronic illness. DM is metabolic diseases with characteristic hyperglycemia that occur di to abnormal insulin secretion, insulin performance or both (ADA, 2010). Depend on PERKENI (2011), complication of DM occur from uncontrolled blood glucose level, such as neuropathy, hypertension, coronary heart disease, retinopathy, nephropathy and gangrene. The people who have high risk of DM are high-carbohydrate diets, have a family history of diabetes Mellitus. there for we need to early detection to be prevention became Diabetes Mellitus disease. Early detection of activities of patients with DM are held at RW 07 due to DM risk faktor that occur in that area. Community Service Activities were carried out on Wednesday, March 23, 2016 at the RW 07 Pekayon village meeting hall. Activities include measuring glucose level and counseling. For the results of early detection blood glucose level, it was found that 56 out of 82 residents experienced and increase in blood glucose level (68%). Most of them carry out consultations related to diet and Diabetes Mellitus family history